2011
DOI: 10.1136/hrt.2010.213041
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on the prognostic value of the N-terminal pro-B-type natriuretic peptide (NT-proBNP) in patients with acute myocardial infarction

Abstract: In this large population of patients with myocardial infarction, circulating NT-proBNP levels were considerably lower in obese patients; the significance of the propeptide level as an independent prognostic factor is severely compromised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
(32 reference statements)
6
16
0
Order By: Relevance
“…Similar findings were reported when troponin and brain natriuretic peptide were used in addition to the TIMI risk score 19. Their addition produced only a slight increase in the c statistic but, as with NT-proBNP, they were able to identify a subgroup of the TIMI high-risk group who were at very high risk of adverse events, and in whom an aggressive approach to drug therapy and interventions might be warranted 18. Damman and colleagues20 examined a cohort of patients undergoing primary percutaneous coronary intervention (PCI) for ST-segment elevation myocardial infarction.…”
Section: Do Biomarkers Add Value?supporting
confidence: 73%
See 1 more Smart Citation
“…Similar findings were reported when troponin and brain natriuretic peptide were used in addition to the TIMI risk score 19. Their addition produced only a slight increase in the c statistic but, as with NT-proBNP, they were able to identify a subgroup of the TIMI high-risk group who were at very high risk of adverse events, and in whom an aggressive approach to drug therapy and interventions might be warranted 18. Damman and colleagues20 examined a cohort of patients undergoing primary percutaneous coronary intervention (PCI) for ST-segment elevation myocardial infarction.…”
Section: Do Biomarkers Add Value?supporting
confidence: 73%
“…This was sixfold higher than the referent group. NT-proBNP was found to be a useful addition across all age groups but not in obese patients, in whom NT-proBNP levels were much lower 18. Similar findings were reported when troponin and brain natriuretic peptide were used in addition to the TIMI risk score 19.…”
Section: Do Biomarkers Add Value?supporting
confidence: 71%
“…Similar findings were reported when troponin and brain natriuretic peptide were used in addition to the TIMI risk score (19). Their addition produced only a slight increase in the c statistic but, as with NT-proBNP, they were able to identify a subgroup of the TIMI high-risk group who were at very high risk of adverse events, and in whom an aggressive approach to drug therapy and interventions might be warranted (18). Damman and colleagues (20) examined a cohort of patients undergoing primary percutaneous coronary intervention (PCI) for ST-segment elevation myocardial infarction.…”
Section: Do Biomarkers Add Value?supporting
confidence: 69%
“…Several recent reports suggest that obesity, as indexed by elevated body mass index (BMI), may also affect NT-proBNP levels, with lower circulating levels in those with higher BMI in subjects with acute or chronic heart failure [2], [3], significant coronary artery disease or acute myocardial infarction [4], [5] and healthy general populations [6]. However, isolated study showed that obesity is not statistically associated with NT-proBNP in asymptomatic patients with hypertension [7].…”
Section: Introductionmentioning
confidence: 99%